Gut microbiome remodeling in chronic kidney disease: implications of kidney replacement therapies and therapeutic interventions - Wang, Qianwei; Han, Yucheng; Pang, Liang; Zhou, Zhicheng; Dai, Lijuan (Frontiers in Medicine, 2025)
The escalating global burden of end-stage renal disease (ESRD), driven by aging populations and rising metabolic comorbidities, underscores the urgent need for innovative therapeutic strategies. Emerging evidence highlights the gut microbiome as a pivotal modulator of renal pathophysiology through the gut-kidney axis, with microbial dysbiosis exacerbating gut microbial metabolites (e.g., uremic toxins), systemic inflammation, and multi-organ damage. This narrative review explores the divergent impacts of kidney replacement therapies (KRT)—hemodialysis (HD) and peritoneal dialysis (PD)—on gut microbiota dynamics: HD is associated with Firmicutes and Proteobacteria enrichment, reduced butyrate-producing taxa (e.g., Faecalibacterium, Roseburia), and systemic microbial translocation; whereas PD-driven glucose absorption and iron supplementation foster pathogenic proliferation (e.g., Enterobacteriaceae) and impair short-chain fatty acid (SCFA) metabolism. Current interventions, including probiotics, prebiotics, plant-based diets (PBDs), and fecal microbiota transplantation (FMT), demonstrate potential in mitigating dysbiosis and uremic toxin accumulation. PBDs reduce inflammatory markers (IL-6, CRP) and lower all-cause mortality risk by 24% in PD patients; synbiotics (e.g., Lactobacillus casei + galactooligosaccharides) reduce serum p-cresyl sulfate by 20% in HD patients; and FMT increases levels of short-chain fatty acids (propionate, butyrate) and lowers trimethylamine N-oxide (TMAO) concentrations in streptozotocin-induced diabetic nephropathy mouse models. However, clinical translation remains challenged by small sample sizes, heterogeneous outcomes, and a lack of hard endpoints. Future research must prioritize standardized protocols, personalized microbial profiling, and synergistic integration of dietary and microbiome-targeted therapies. Bridging mechanistic insights with clinical validation will advance precision medicine in ESRD management, offering transformative potential for patients burdened by this therapeutic impasse.